Role of filtering and biodeposition by Adamussium colbecki in circulation of organic matter at Terra Nova Bay (Ross Sea, Antarctica) - CHIANTORE, MARIACHIARA; CATTANEO VIETTI, RICCARDO; ALBERTELLI, GIANCARLO; MISIC, CRISTINA; FABIANO, MAURO (Journal of Marine Systems, 1998)
At Terra Nova Bay, the scallop Adamussium colbecki Smith, 1902. characterises the soft and hard bottoms from 20 to 80 m depth, constituting large beds and reaching high values of density 50–60 individualsrm2. and biomass 120 grm2 DW soft tissues. To assess its role in the organic matter recycling in the coastal ecosystem, its filtering and biodeposition rates were evaluated in laboratory experiments during the austral summer 1993r94. Filtration rates, measured in a flow-through system, were calculated from the difference in particulate organic carbon POC., nitrogen PON. and chlorophyll-a Chl-a. concentration in inflow and outflow water. Experiments were performed using natural sea water with POC, PON and Chl-a concentrations of about 450 mgrl, 90 mgrl and 2 mgrl, respectively. The biodeposition rate and the biochemical composition of the biodeposits were studied in order to detect how the organic matter is transformed through feeding activity of A. colbecki. At q18C temperature, the average filtering rate was about 1 l hy1 gy1 DW soft tissues. in specimens ranging in body mass from 2 to 3 g DW soft tissues. and 6–7 cm long. The biodeposition rate in 3–8 cm long specimens, ranging from 0.4 to 5.7 g DW soft tissues., was about 5.65 mg DWrg DWrday, leading to an estimate of Corg flux, through biodeposition by A. colbecki, of about 21 mg C my2 dayy1 at in situ conditions. Comparison between the biochemical composition of seston and biodeposits shows a decrease of the labile compounds, of the Chl-arphaeopigments ratio in the biodeposits. The recorded CrN ratio decrease suggests a microbial colonisation in the biodeposits. This study suggests that Adamussium colbecki plays an important role in coupling the material fluxes from the water column to the sea bed, processing about 14% of total Carbon flux from the water column to the sediments, with an assimilation efficiency of 36%.